Analisis Potensi Ekonomi Pada Sektor Dan Subsektor Pertanian, Kehutanan Dan Perikanan Di Kabupaten Tambrauw Tahun 2013 -2017 - Sisilia Maria Parinusa (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2019)
Agriculture, forestry and fishery sector has an important role in generating the economic growth in Tambrauw Regency. It can be seen from the amount of its contribution to the gross value added which is more that 33 percent. The aim of this study is to identify and analyse the potential subsector of agriculture, forestry and fisheries sector in Tambrauw Regency. By using Location Quotient (LQ) Method and Shift Share analysis and supported by a time series data of GDP growth between the study area and reference area in the recent five years the potential subsectors can be determined. The research result reveals that food plant, horticulture group and forestry and logging subsector are the potential subsectors to promote the regional income due to their location quotient greater than 1 and have positive competitive advantage values.